Commentary: Increasing productivity, meat yield, and beef quality through genetic selection, management, and technology - Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 2013)
The primary purpose of producing beef cattle is to convert grass, forages, and various byproducts, plus human-edible protein and energy, into highly nutritious and tasty beef. To accomplish this, (1) cattle enterprises must be profitable; (2) carcasses should yield a high percentage of meat; (3) beef should be safe, affordable, attractive, nutritious, and highly palatable; and (4) both production and processing systems must be socially and environmentally responsible. The U.S. population has doubled since 1952, but the number of cows in the U.S. is the lowest since the 1950s. At the same time, a rather dramatic increase in beef production has occurred because of improved genetics, management, and technology. Yet, too many cattle breeders and/or breed associations have failed to realize improvements in meat yield, marbling, and palatability through genetic selection for these traits. Consequently, a significant proportion of cattle are fed to excessive fatness with long feeding periods to attain Choice or Prime marbling. Waste fat production is very costly to the industry. An extensive review, evaluation, and interpretation of research literature, technical bulletins, trade articles, and industry trends demonstrates a path forward through improved genetics, improved management, and optimum use of technology to improve production efficiency, meat yield, and meat quality of cattle.
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-162-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1083; Beef; Productivity; Yield; Quality; Genetics; Technology; Tenderness